Reaction of plasma adiponectin level in non-small cell lung cancer patients treated with EGFR-TKIs - Umekawa, Kanako; Kimura, Tatsuo; Kudoh, Shinzoh; Suzumura, Tomohiro; Nagata, Misato; Mitsuoka, Shigeki; Matsuura, Kuniomi; Oka, Takako; Yoshimura, Naruo; Kira, Yukimi; Hirata, Kazuto (Osaka City medical journal, 2013)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are routinely used to treat advanced non-small cell lung cancer (NSCLC) patients with activated EGFR mutations, and are associated with excellent response and improvement of performance status. Adipose tissue produces and releases substances called adipokines, which include adiponectin, leptin, resistin, and hepatocyte growth factor (HGF), etc. Previously, we reported that high levels of plasma HGF at diagnosis indicated intrinsic resistance to EGFR-TKIs. EGFR-TKIs have been hypothesized to affect these adipokines. This prospective study, to evaluate the correlation between plasma adiponectin and insulin levels and non-hematological adverse effects in advanced NSCLC following EGFR-TKIs administration, was conducted at the Osaka City University Hospital. Plasma adiponectin and insulin levels were determined at diagnosis and on treatment day 30. Overall 33 patients were enrolled. We obtained plasma samples for analyses from all patients at diagnosis and from 26 patients on day 30. Increased adiponectin (13.69 to 14.42 microg/mL, p = 0.0092), and decreased insulin (404.0 to 351.2 pg/mL, p = 0.022) were observed after EGFR-TKI treatments. High levels of adiponectin at diagnosis were associated with severities of skin rash (p = 0.035). The adiponectin was affected by EGFR-TKI treatments for NSCLC. Besides, the adverse events by EGFR-TKIs were influenced by the plasma adipokines at diagnosis. Our study may provide useful information regarding patient outcomes to EGFR-TKI treatments. A prospective large clinical trial is warranted to clarify these results.